Two versions of heterotopia: The role of art practices in participative urban renewal processes. (June 2019) - Sacco, Pier Luigi; Ghirardi, Sendy; Tartari, Maria; Trimarchi, Marianna
Abstract: The purpose of this paper is to take part in the debate about power relationships in contemporary cities between the agents of urban renewal and the local communities, as mediated by cultural and artistic interventions and projects. Our study proposes a new conceptual frame, focused on the comparison between two notions of heterotopia as theoretical alternatives for the interpretation of cities as social and participatory spaces. The notions we consider may be traced to two key thinkers such as Michel Foucault and Henri Lefebvre, and lay the foundation for alternative analytical paradigms of the contemporary urban condition, in relation to artistic and cultural practices in the public space. We draw upon these two alternative readings of heterotopia to explore the implications of the interaction of artistic practices with the urban space as a contested terrain from the viewpoint of power relationships. In our analysis, we find that Foucault's notion of heterotopia is potentially conducive to top-down planning processes and to gentrification. Lefebvre's notion is instead possibly more suited to participatory practices as strategies of reactivation of the right to the city. Highlights: We critically compare Foucault and Lefevbre notions of heterotopia. We analyze their different implications for participative arts and culture practice. We connect local community empowerment to reclaiming the right to the city. We critically discuss how art in the public domain can favor of block such reclamation.